ALTERNATIF STRATEGI PENINGKATAN DAYA SAING SMA KRISTEN 2 SALATIGA - Nindiarini, Innes Septa; Sulasmono, Bambang Suteng (Kelola: Jurnal Manajemen Pendidikan, 2015)
This research and development aims to formulate strategic plan to enhancing competitiveness in SMA Kristen 2 Salatiga. Data were gathered by means of Focus GroupÂ Discussion (FGD), interview, questionnaire, and documentation study. Fishbone analysisÂ is used to identify the root causes of low school competitiveness. The analysis wasÂ categorized based on five factors i.e. reputation, school resources, information andÂ technology, human resource, and partnership. Based on the analysis, the strategies areÂ formulated with educational reengineering approach as follows: 1) reconstructing school image by improving academic and non academic achievement, 2) developing innovativeÂ curriculum based on outdoor experience and IT, 3) increasing student discipline, 4)optimizing IT usage on promotion and marketing, 5) improving the quality of schoolÂ programs, 6) developing entrepreneurship programs, 7) improving the quantity and qualityÂ school infrastructures, 8) improving teachersâ skill and competence of IT, 9) enhancingÂ the role of school board, 10) maximizing the role of parents, alumnae, and other institutionÂ to develop the school programs, and 11) establishing a vocational high school. It isÂ recommended for the school to have cooperation with the stakeholder and the schoolÂ board to implement the strategic plan so that the competitiveness will enhance in the future.